Probiotic supplementation in marathonists and its impact on lymphocyte population and function after a marathon: a randomized placebo-controlled double-blind study - Batatinha, Helena; Tavares-Silva, Edgar; Leite, Geovana S. F.; Resende, Ayane S.; Albuquerque, José A. T.; Arslanian, Christina; Fock, Ricardo A.; Lancha, Antônio H.; Lira, Fabio S. [UNESP]; Krüger, Karsten; Thomatieli-Santos, Ronaldo; Rosa-Neto, José C. (Springer Nature, 2020)
Probiotic supplementation arises as playing an immune-stimulatory role. High-intensity and -volume exercise can inhibit immune cell function, which threatens athletic performance and recovery. We hypothesized that 30 days of probiotic supplementation could stabilize the immune system of athletes preventing immune suppression after a marathon race. Twenty-seven male marathonists were double-blinded randomly into probiotic (Bifidobacterium-animalis-subsp.-Lactis (10 × 109) and Lactobacillus-Acidophilus (10 × 109) + 5 g of maltodextrin) and placebo (5 g of maltodextrin) group. They received 30 sachets and supplemented 1 portion/day during 30 days before the race. Blood were collected 30 days before (rest), 1 day before (pre), 1 h after (post) and 5 days after the race (recovery). Both chronic and acute exercise modulated a different T lymphocyte population (CD3+CD4−CD8− T-cells), increasing pre-race, decreasing post and returning to rest values at the recovery. The total number of CD8 T cell and the memory subsets statistically decreased only in the placebo group post-race. Pro-inflammatory cytokine production by stimulated lymphocytes decreased in the probiotic group after the supplementation period. 30 days of probiotic supplementation maintained CD8 T cell and effector memory cell population and played an immunomodulatory role in stimulated lymphocytes. Both, training and marathon modulated a non-classical lymphocyte population regardless of probiotic supplementation.